Pengaruh Pemanfaatan Media Pembelajaran Terhadap Aktivitas Siswa - Ansharullah Ansharullah; Ristiliana Ristiliana (Lembaga penelitian dan pengabdian kepada masyrakat, 2012)
This research consists of two variables they are utilizing teaching by the teacher (independent variable or X variable) and students activities (dependent variable or Y variable). The problem which will be discussed in this study is the influence between both variables it is the influence of utilizing teaching media by the teacher toward students activities. The purpose of this study is whether there is significant effect between utilizing teaching media toward students activities in the study of integrated social studies.